Assessing the Indonesian government's compliance with the public information disclosure law in the context of COVID-19 data transparency - Khadafi, Rizal; Nurmandi, Achmad; Hasibuan, Effiati Juliana; Harahap, Muhammad Said; Saputra, Agung; Mahardika, Ananda; Izharsyah, Jehan Ridho (Frontiers in Political Science, 2024)
The matter of transparency regarding information and data emerges as a pivotal concern in the context of mitigating the COVID-19 epidemic in Indonesia. The regulation of public information transparency in Indonesia is stipulated in Law Number 14 of 2008, which ensures the disclosure of public information. The objective of this study is to conduct a comprehensive examination of the extent to which the Government of Indonesia adheres to the principles outlined in its legislation with regard to the implementation of transparency throughout the pandemic. The approach employed to assess the degree of adherence is normative-empirical analysis. The findings of this research analysis indicate a significant lack of transparency in the public dissemination of COVID-19 information and data in Indonesia. This lack of transparency is inconsistent with the provisions outlined in Law No. 14 of 2008, which governs the publication of public information in the country. The act of downplaying COVID-19 through the dissemination of information, along with the government's decision to withhold comprehensive data, and the prevailing skepticism towards scientific research might be characterized as efforts to impede citizens' access to precise knowledge.